2001
DOI: 10.1101/gad.860301
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation controlled by alternatively spliced isoforms inactivates the QUAKING apoptotic inducer

Abstract: The quaking viable mice have myelination defects and develop a characteristic tremor 10 d after birth. The quaking gene encodes at least five alternatively spliced QUAKING (QKI) isoforms that differ in their C-terminal 8-30-amino-acid sequence. The reason for the existence of the different QKI isoforms and their function are unknown. Here we show that only one QKI isoform, QKI-7, can induce apoptosis in fibroblasts and primary rat oligodendrocytes. Heterodimerization of the QKI isoforms results in the nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 49 publications
3
94
1
Order By: Relevance
“…13,17) These results clearly suggest the involvement of the gld-1 in the regulation of cell proliferation. More importantly, Pilotte et al 33) recently reported that the QKI-7 isoform could act as a potent apoptosis inducer in vitro. QKI protein and possibly Hqk gene product function as RNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,17) These results clearly suggest the involvement of the gld-1 in the regulation of cell proliferation. More importantly, Pilotte et al 33) recently reported that the QKI-7 isoform could act as a potent apoptosis inducer in vitro. QKI protein and possibly Hqk gene product function as RNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…32) Furthermore, it was recently reported that one particular protein isoform of the qkI, QKI-7 is a potent inducer of apoptosis. 33) It is thus possible that the Hqk gene is involved in cell proliferation as well as disease development processes. As an initial step towards understanding the potential roles of Hqk gene in disease development, we have isolated both cDNA and genomic clones for Hqk, characterized its genomic structure and determined its expression pattern, as well as the chromosomal location of Hqk.…”
Section: )mentioning
confidence: 99%
“…Genes encoding several proapoptotic proteins, including JNK1, lymphotoxin beta-receptor, quaking protein-7 and granzyme F, [38][39][40] were strongly upregulated in C3 lenses. C3 toxin has been reported to activate the JNK stress-signaling pathway and increased apoptosis in cell culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…1). KH domain-containing RNA binding proteins have been proposed as a family of apoptotic inducers (2). For example, the mouse quaking (QKI) protein and the Drosophila Kep1 and Sam50 proteins are potent inducers of cell death in the absence of any other signal (2)(3)(4).…”
mentioning
confidence: 99%
“…For example, the mouse quaking (QKI) protein and the Drosophila Kep1 and Sam50 proteins are potent inducers of cell death in the absence of any other signal (2)(3)(4). Expression of QKI causes apoptosis in transfected cells (4), and the C-terminal 14 aa of the QKI-7 isoform are necessary and sufficient to induce apoptosis (2). Kep1 (also referred to as Qkr58E-3; ref.…”
mentioning
confidence: 99%